Critical successful factors analysis for national data infrastructure implementation - Al Shamsi, Sulaiman; Ahmad, Anuar (2008)

(untitled)
Information is an expensive resource, and for this reason appropriate information and the resources to fully utilize this information may not always be readily available, particularly in the developing country.Many national, regional, and international programs and projects are working to improve access to available spatial data, promote its reuse, and ensure that additional investment in spatial information collection and management results in an ever growing, readily available and useable pool of spatial information. In regions characterized by an availability of geographic information, in combination withthe power of Geographic Information Systems (GIS), decision support tools, data bases, and the World Wide Web and their associated interoperability, the way better-resourced communities address critical issues of social, environmental, and economic importance is changing rapidly. The available computing infrastructure, available legal arrangements and full understandings of countries systems, legal and economical position for a given country could be the key for organizing, hosting and handling national spatial data on the national level. Furthermore technology has reached a point were every body can share information on real time. The study will describes different spatial data experiences in sharing and visualizing spatial data using different frameworks such as spatial data infrastructures, centric databases and distributed spatial data. The main problem is many professionals feel that ready made solutions could solve the problem regardless the nature, habits and the culture of the countries. Developed countries have huge computing infrastructures which make data handling and sharing through local and global networks easy and mandatory for every user. However, developing and undeveloped countries could have a lack in the computing infrastructure. A good running computer networks could be a major problem of having efficient system to share and handle geospatial data. Therefore a good understanding for the property and the criteria of a given national geospatial data is important to have an effective national geospatial framework in a given country. Enterprise GIS implementations are costly, and yet this seems to be the direction adopted by organizations tackling the initiative for the first time and often for the second or third time. Why do organizations take this approach? How is success measured? Are there techniques that can ensure success of enterprise GIS implementations? In discussing strategies for successful enterprise GIS implementation, it should remain evident that each organization is ultimately unique, having its own culture, business practices, methodologies, and processes. An adopted system that works for one organization will not necessarily be adequate or appropriate for another organization. The nature of the organization, and the people that work within it, will shape the way technology is accepted and used by the corporation or organization. Consideration must be given to the complex, "political" nature of the organization. It cannot be assumed that individuals will behave professionally, or rationally, rather than according to personal agendas (Haley, 2007).